Linking clinical and imaging diagnostic assessments of the feline hypertrophic cardiomyopathy phenotype - de Sousa, Felipe Gaia; Muzzi, Ruthnea Aparecida Lazaro; de Araújo, Roberto Baracat; Faleiros, Rafael Resende; Queiroz, Fabiana Silva Fádel; Beier, Suzane Lilian (Frontiers in Veterinary Science, 2025)
Hypertrophic cardiomyopathy (HCM) phenotype represents the most commonly diagnosed cardiac disorder in felines, characterized by heterogeneous clinical presentations and a well-established genetic basis. This study aims to integrate clinical, laboratory, and imaging diagnostic assessments of the feline HCM phenotype, providing a comprehensive perspective on how complementary diagnostic approaches enhance disease understanding and precision. The HCM phenotype is defined by concentric hypertrophy of the left ventricular free wall and/or interventricular septum, often accompanied by secondary left atrial remodeling due to chronic pressure and volume overload. Clinical signs typically emerge with disease progression, frequently culminating in congestive heart failure (CHF) and respiratory signs; however, some cats may remain asymptomatic. Accurate diagnosis of the HCM phenotype requires an integrative approach combining thorough clinical evaluation and advanced imaging modalities to avoid misdiagnosis, which may negatively impact prognosis and quality of life. Detailed clinical history and physical examination are essential for diagnostic orientation, particularly in symptomatic patients. Routine laboratory tests support systemic assessment, although no pathognomonic biomarker has been identified to date. Cardiac biomarkers such as atrial natriuretic peptide (ANP), N-terminal pro–B-type natriuretic peptide (NT-proBNP), and cardiac troponin I (cTnI) provide complementary diagnostic information, albeit with lower sensitivity than imaging techniques. While electrocardiography may reveal conduction disturbances suggestive of HCM, transthoracic echocardiography remains the diagnostic gold standard. In addition to confirming the diagnosis, echocardiographic evaluation allows for disease staging, longitudinal monitoring, and evidence-based therapeutic decision-making. Our study reinforces the need for an integrated diagnostic framework that combines clinical examination, laboratory testing, and imaging evaluation. By promoting a multidimensional diagnostic perspective, this study contributes to refining the understanding of the feline HCM phenotype and supports the development of more precise diagnostic and therapeutic strategies, ultimately improving clinical outcomes in affected cats.